Trends in achieving nutritional status aged 0-23 months based on the TB/U index against the median line for 2019-2022 in Madina Regency - Yessi Septia Tampubolon; Haripin Togap Sinaga; Evlin SH Sitinjak (Jurnal Ilmiah Kesehatan)
Child growth trends are used to compare weight gain and body length or height with